Angiotensin II type 2 receptor (AT2R) localization and antagonist‐mediated inhibition of capsaicin responses and neurite outgrowth in human and rat sensory neurons. (17th December 2012) - Anand, U.; Facer, P.; Yiangou, Y.; Sinisi, M.; Fox, M.; McCarthy, T.; Bountra, C.; Korchev, Y.E.; Anand, P.
Abstract Background The angiotensin II (AngII) receptor subtype 2 (AT2R) is expressed in sensory neurons and may play a role in nociception and neuronal regeneration. Methods We used immunostaining with characterized antibodies to study the localization of AT2R in cultured human and rat dorsal root ganglion (DRG) neurons and a range of human tissues. The effects of AngII and AT2R antagonist EMA401 on capsaicin responses in cultured human and rat (DRG) neurons were measured with calcium imaging, on neurite length and density with Gap43 immunostaining, and on cyclic adenosine monophosphate (cAMP) expression using immunofluorescence. Results AT2R expression was localized in small‐/medium‐sized cultured neurons of human and rat DRG. Treatment with the AT2R antagonist EMA401 resulted in dose‐related functional inhibition of capsaicin responses (IC50 = 10 nmol/L), which was reversed by 8‐bromo‐cAMP, and reduced neurite length and density; AngII treatment significantly enhanced capsaicin responses, cAMP levels and neurite outgrowth. The AT1R antagonist losartan had no effect on capsaicin responses. AT2R was localized in sensory neurons of human DRG, and nerve fibres in peripheral nerves, skin, urinary bladder and bowel. A majority sub‐population (60%) of small‐/medium‐diameter neuronal cells were immunopositive in both control post‐mortem and avulsion‐injured human DRG; some very small neurons appeared to be intensely immunoreactive, with TRPV1 co‐localization. While AT2R levels were reduced in human limb peripheral nerve segments proximal to injury, they were preserved in painful neuromas. Conclusions AT2R antagonists could be particularly useful in the treatment of chronic pain and hypersensitivity associated with abnormal nerve sprouting.